New Product Introduction Prize (NPIP) and the Market Value of the Firm: An Empirical Investigation into the Computer, Electronic and Communication Industry (CECI) - Quaye, Isaac; Mu, Yinping; Abudu, Braimah; Sarbah, Alfred (Archives of Business Research, 2018)
This research studies the effect of new product introduction prize (NPIP) announcements on firm value, applying event study methodology to 509 NPIP announcements between the period of 2001-2015. Specifically, the study focuses on NPIP announcements made in the computer, electronic and communication industry (CECI). It analyzes the short-term effect of market value caused by NPIP announcements within two-day event window (Days -1 and 0) by using market model. We established that NPIP announcements are perceived by investors as positive news, resulting in significant positive cumulative abnormal returns (CARs). Having controlled for firm-specific effects, (reputation and R&D intensity), we observed that stock market responds more positively to NPIPs attained by small-sized firms than large-sized firms. In addition, stock market reaction to firms that won NPIP from third-party prize schemes is more positive than winning from prize schemes within the firms’ supply chain. Due to the indispensable financial rewards accumulated by firms winning NPIPs, the conclusions of this research are very valuable to managers in the allocation of more resources towards augmenting their firms’ new product development capabilities.